2007
DOI: 10.1002/asna.200610748
|View full text |Cite
|
Sign up to set email alerts
|

A new numerical method for solving radiation driven winds from hot stars

Abstract: We present a general method for solving the non-linear differential equation of monotonically increasing steady-state radiation driven winds. We graphically identify all the singular points before transforming the momentum equation to a system of differential equations with all the gradients explicitly give. This permits a topological classification of all singular points and to calculate the maximum and minimum mass-loss of the wind. We use our method to analyse for the first time the topology of the non-rota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We conclude that kinks arise when we use an initial (trial) solution that belongs to a different solution branch in the topology of the m-CAK model (see topological analysis by Curé & Rial 2007).…”
Section: D Time-dependent Wind Solutions For Rotating Starsmentioning
confidence: 90%
See 3 more Smart Citations
“…We conclude that kinks arise when we use an initial (trial) solution that belongs to a different solution branch in the topology of the m-CAK model (see topological analysis by Curé & Rial 2007).…”
Section: D Time-dependent Wind Solutions For Rotating Starsmentioning
confidence: 90%
“…All singular point are labeled from A to E clockwise starting from the Fast solution eigenvalues as shown in Table A1. This table also show the location of the each singular point in the u, η plane and the value of the determinant of matrix B, that give us the information concerning the topology type of a singular point (see definition of matrix B in section 5.2 from Curé & Rial 2007). In all these cases, the determinant values were negative, thus all singular points are X-type.…”
Section: Appendix A: Topological Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…Based on the m-CAK theory, Gormaz-Matamala et al (2019, hereafter Paper I) developed a prescription to derive self-consistent solutions given different sets of stellar parameters for hot massive stars, following the quasi-NLTE treatment for atomic populations of Mazzali & Lucy (1993), the radiation field calculated from Tlusty (Hubeny & Lanz 1995) and the hydrodynamic solutions performed by HydWind (Curé 2004;Curé & Rial 2007). Paper I demonstrated that the prescription provided useful theoretical wind parameters for different sets of temperature, surface gravities, abundances and even the rotational velocity.…”
Section: Introductionmentioning
confidence: 99%